Perlindungan Hukum dan Batas Pertanggungjawaban Direksi dalam Pengelolaan Perusahaan Publik Berdasarkan UU Perseroan Terbatas - Hazzar, Salsa (Jurnal Hukum Positum, 2025)
This study aims to analyze the responsibility of the board of directors in managing public companies based on Law Number 40 of 2007 concerning Limited Liability Companies (UUPT), particularly in the implementation of Article 97, which regulates the legal responsibility of the directors. In practice, the main challenge arises in proving the fault or negligence of the directors, especially when decisions made are high-risk but have significant consequences for the company. This research delves deeper into the concepts of fiduciary duty, business judgment rule, and the application of good corporate governance principles within the Indonesian legal context, which play a crucial role in determining whether the directors have acted in accordance with their legal obligations. Furthermore, this study identifies the legal uncertainties arising from differing interpretations regarding the responsibility of directors in various corporate cases, which affect investor confidence and the stability of the capital market. By using a normative juridical approach and case analysis, this research is expected to contribute to clarifying the legal protection mechanisms for directors and offer recommendations for regulatory improvements to create better legal certainty in the management of public companies in Indonesia.